Jaminan Konstitusi Pemberdayaan Universal Terhadap Penyandang Disabilitas Tereksploitasi di Jalanan - Ghatfhan Hanif (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The mandate of the introduction of human rights and freedom as a human being has been stated in the opening of the 1945 Constitution (UUD 1945) with 4 (four) paragraphs that lead humans and their nation to humanity, a justice that is independent, united, sovereign, just and prosperous and is based on the development of the nation's ideals in the crystallization of Pancasila. The constitution is like the 'Spirit of the state' that lives to grow, develop, and direct the 'Physical state' towards the paradigm, understanding and actualization of axiology in everyday life. The reason is, the state is said to be perfect if its physicality is filled with spirit in the rules of harmony, harmony and balance. Thus, all of this is needed to be a name